Z-8z=6z-7-z

Simple and best practice solution for Z-8z=6z-7-z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Z-8z=6z-7-z equation:


Simplifying
Z + -8z = 6z + -7 + -1z

Reorder the terms:
Z + -8z = -7 + 6z + -1z

Combine like terms: 6z + -1z = 5z
Z + -8z = -7 + 5z

Solving
Z + -8z = -7 + 5z

Solving for variable 'Z'.

Move all terms containing Z to the left, all other terms to the right.

Add '8z' to each side of the equation.
Z + -8z + 8z = -7 + 5z + 8z

Combine like terms: -8z + 8z = 0
Z + 0 = -7 + 5z + 8z
Z = -7 + 5z + 8z

Combine like terms: 5z + 8z = 13z
Z = -7 + 13z

Simplifying
Z = -7 + 13z

See similar equations:

| 2(3a^2-1)-6a=5a | | 7x+3y=9.20 | | 0=x-0.04x^2 | | 8x=1x^2 | | 9(4x+1)=5x-6x | | 16+8=-4(5x-6) | | 26x*5= | | BX+GY=K | | 4+2x=4x-4 | | 8z-z=-2+3z-1-5 | | 3x+105=180 | | 19x+17x=180 | | j=c(1+RT) | | 8x-3=32x+15 | | -x+3=7X+8 | | 3x-(-2)=-4 | | 3(x+5)=9 | | -9=8b-1 | | 0.75x-3=9 | | x-3x+14=0 | | 2w^2+4w=-3 | | -6x+8=14 | | A=171(19+15) | | -3n+8=-7 | | 5(2x+5)=-22+7 | | (9b-27)=36 | | A=85(10+2) | | (12n-8)=26 | | 4x+73x=19+x | | (5k+35)-8=12 | | 8z-z=-3+2z-3-9 | | (5k+35)-8=112 |

Equations solver categories